Tinjauan Aspek Budaya pada Pembelajaran IPA: Pentingnya Pengembangan Kurikulum IPA - Fajar Hardoyono (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
: Education deals with enlightening people and developing human resources. The reasecher concluded that cultural background of students influences their learning attitude in the school. Therefore, the developing learning process of Natural Sciences insist student to elaborate principles of Natural Sciences without ignoring cultural valuesof local community. The policy of decentralization of Indonesian Government had authorized and legitimated local authorities to develop curriculum based on the local cultures. To do so, each local government through the officers of Education has to create a curiculum by involving some curriculum experts, instructures, natural sciences theachers, and the lectures of universities who adequately understand learning model of Natural Sciences.